An audit to assess the outcome of the babies diagnosed with patent foramen ovale (PFO) and patent ductus arteriosus (PDA) on initial echocardiograms. (7th June 2011) - Singh, Y; Mukherjee, A; Bustani, P
Abstract : Background: Patent foramen ovale (PFO) and/or patent ductus arteriosus (PDA) are common findings on echocardiograms carried out in the newborn period for heart murmurs or family history (FH) of congenital heart disease (CHD). Our routine practice has been to offer follow-up by Neonatologists with echo skills in case of a missed diagnosis. Aims and objectives: We sought to assess the outcome PFO or PDA detected on an early echocardiogram carried out in the newborn period. Methods: Retrospective observational analysis of all patients attending neonatal cardiac follow-up clinics at Jessop Wing, Sheffield, between August 2007 and December 2008. PFO and PDA were defined as small (<2 mm), moderate (2–4 mm) and large (>4 mm). Results: 113 patients with no significant cardiac pathology on echo were followed up in the neonatal cardiac outpatient clinics. 34 had a FH of CHD and 65 had a newborn murmur. Two had a large PDA, one had a large PFO. The rest were normal or small or moderate PDA's and PFO's. Three patients (all with positive FH) were found to have an ASD. Two had long term follow-up for persistent moderate PFO. One developed mild aortic stenosis, one mild pulmonary stenosis. One with congenital rubella syndrome needed duct ligation. Conclusions: An early scan performed for newborn murmur which shows PFO and or PDA is likely to resolve. A clinical assessment for murmur by a GP could detect those infants who may need a repeat echo for evolving or missed initial diagnosis.